Analysis Of Islamic Enterpreneurs Knowledge, Motivation and Social Support On Interest Of Business Of College Students Moslem In Semarang - Qristin Violinda; Heri Prabowo; Ika Indriasari (International Journal of Halal System and Sustainability, 2022)
The era of the ASEAN Economic Community (MEA) present a difficult challenge for the people of Indonesia. Opportunities and competition Faced by its People will be increased exponentially. In this era where the opportunity to get a job will of course also be competitively increased, will create a fairly high unemployment rate. One way to reduce the unemployment is to create an independent business or entrepreneurship. This study aim is to measure the extent to which Islamic entrepreneurial knowledge, motivation and social support have an influence on the interest in entrepreneurship. The type of research used is quantitative research using a sampling technique called simple random sampling. The sample in this study amounted to 120 respondents with 117 questionnaires used. The Processing Software used in this research are SPSS Version 21.0. Based on the results of statistical tests with multicollinearity analysis, shows that Islamic entrepreneurial knowledge had the highest influence and contribution to the interest of student moslem entrepreneurship at 79.1%, Motivation had an influence and contribution to the interest of student moslem entrepreneurship in Semarang by 69.4% while social support had almost no influence on entrepreneurship interests as it only has a very small contribution of 14.3%.